Metabolism of very-low-density lipoprotein and chylomicrons by streptozotocin-induced diabetic rat heart: effects of diabetes and lipoprotein preference. - Niu, Y; Evans, R (2008)
Very-low-density lipoprotein (VLDL) and chylomicrons (CM) are major sources of fatty acid supply to the heart, but little is known about their metabolism in diabetic myocardium. To investigate this, working hearts isolated from control rats and diabetic rats 2 wk following streptozotocin (STZ) injection were perfused with control and diabetic lipoproteins. Analysis of the diabetic lipoproteins showed that both VLDL and CM were altered compared with control lipoproteins; both were smaller and had different apolipoprotein composition. Heparin-releasable lipoprotein lipase (HR-LPL) activity was increased in STZ-induced diabetic hearts, but tissue residual LPL activity was decreased; moreover, diabetic lipoproteins stimulated HR-LPL activity in both diabetic and control hearts. Diabetic hearts oxidized lipoprotein-triacylglycerol (TAG) to a significantly greater extent than controls (>80% compared with deposition as tissue lipid), and the oxidation rate of exogenous lipoprotein-TAG was increased significantly in diabetic hearts regardless of TAG source. Significantly increased intracardiomyocyte TAG accumulation was found in diabetic hearts, although cardiac mechanical function was not inhibited, suggesting that lipotoxicity precedes impaired cardiac performance. Glucose oxidation was significantly decreased in diabetic hearts; additionally, however, diabetic lipoproteins decreased glucose oxidation in diabetic and control hearts. These results demonstrate increased TAG-rich lipoprotein metabolism concomitant with decreased glucose oxidation in type 1 diabetic hearts, and the alterations in cardiac lipoprotein metabolism may be due to the properties of diabetic TAG-rich lipoproteins as well as the diabetic state of the myocardium. These changes were not related to cardiomyopathy at this early stage of diabetes.